Implementation of problem based learning model assisted by powerpoint and space building props on the surface area of cubes and beams in fourth grade students SDN Teluk Pucung I - Sativa, Oriza; Putri, Dena Aryani; Aliyatun, Aliyatun; Fakor, Fakor; Sahabudin, Sahabudin (Sekolah Pascasarjana UPI, 2024)
One of the efforts to overcome students' low understanding of the material surface area of cubes and blocks is through the application of innovative learning models. The research aims to improve students' understanding of the material of the surface area of cubes and blocks through Problem Based Learning models assisted by powerpoint media and props for building cubes and blocks. The study used the collaborative classroom action research model of Kemmis Mc Taggart. The participants of the study were 16 students consisting of 10 female students and 6 male students in grade VI SDN Teluk Pucung I. Researchers collected data through observation, interview, and test techniques. Observation and interview techniques are useful for obtaining data on the implementation of research. Meanwhile, test techniques are used to measure students' understanding in the form of description questions. Researchers analyze data through three stages, namely reducing data, presenting data, and drawing conclusions. The data that has been analyzed is then validated through triangulation techniques. Research findings show an improvement in reading skills in each cycle. Referring to the research findings, the researcher concluded that the application of the Problem Based Learning model assisted by powerpoint media and teaching aids for building cubes and blocks can increase students' understanding of the material surface area of cubes and blocks